2007
DOI: 10.1007/s11082-007-9060-1
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of 1.55 μm single transverse mode large diameter electrically pumped VECSEL

Abstract: International audienceWe report on the design, fabrication, and characterization of InP-based 1.55 μm wavelength large diameter (50 μm) electrically pumped vertical external cavity surface emitting lasers (EP-VECSELs). The hybrid device consists of a half vertical cavity surface emitting laser (1/2-VCSEL) structure assembled with a concave dielectric external mirror. The 1/2-VCSEL is monolithically grown on InP substrate and includes a semiconductor Bragg mirror and a tunnel junction for electrical injection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The high thermal conductivity value of Table 1 was used for the dielectric materials in the calculation The R th values measured on the fabricated chips are reported in Table 2. The value previously measured for a 1/2-VCSEL chip with InP/InGaAlAs Bragg mirror on InP substrate (Bousseksou et al 2006) is also reported for comparison. As can be seen the GaAs/AlAs hybrid mirror leads to the best R th values as predicted by the simulations.…”
Section: /2-vcsel Fabrication and Thermal Characterizationmentioning
confidence: 82%
See 2 more Smart Citations
“…The high thermal conductivity value of Table 1 was used for the dielectric materials in the calculation The R th values measured on the fabricated chips are reported in Table 2. The value previously measured for a 1/2-VCSEL chip with InP/InGaAlAs Bragg mirror on InP substrate (Bousseksou et al 2006) is also reported for comparison. As can be seen the GaAs/AlAs hybrid mirror leads to the best R th values as predicted by the simulations.…”
Section: /2-vcsel Fabrication and Thermal Characterizationmentioning
confidence: 82%
“…Prior to VECSEL operation, the thermal resistance of the 1/2-VCSEL chips has been estimated following the method used in Bousseksou et al (2006) for electrically pumped VECSEL. The effective thermal resistance R th is deduced from the shift of the half-cavity mode peak wavelength (corresponding to the photoluminescence signal -PL-) with both absorbed CW pump power, and temperature (measured at low focused power).…”
Section: /2-vcsel Fabrication and Thermal Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical and Electrical Pumping VECSEL lasers have been made with two types of excitation: optical [18,22] and electrical (Chapter 7) [92,93,141,[150][151][152][153]. Electrical excitation of the laser by a diode current injection across a p-n junction is very appealing, as it requires only a simple low-voltage current source to drive the laser, rather than separate pump lasers with their pump optics and power supplies.…”
Section: 33mentioning
confidence: 99%
“…Using wafer fusion with GaAssubstrate-based mirrors, the InGaAlAs/InP active region has demonstrated still higher VECSEL powers of 2.6 W [97,98]. Electrically pumped VECSELs have also been fabricated with 1550 nm emission wavelengths using InP-based material system [92,93,152].…”
Section: Demonstrated Power Scaling and Wavelength Coveragementioning
confidence: 99%